Vers une maturité des territoires périurbains ? - Martine Berger; Claire Aragau; Lionel Rougé (EchoGéo)
The periurban areas around big cities are mostly described as places where residential mobility as well as commuting involve long-range exchanges? with the inner city. Both census data outlining major changes during the last decades, and qualitative surveys conducted on households, highlight the inflection of mobility trends in periurban areas around Paris. Beyond the social and generational diversification of periurban households, some major figures appear, which highlight a will to improve their anchor in the places of residence and to focus mobility on local territories.